Medicine by design : the architect and the modern hospital, 1893-1943 - Adams, Annmarie (Architecture, landscape, and American culture series., 2008)
Medicine by Design examines how hospital design influenced the development of twentieth-century medicine and demonstrates the importance of these specialized buildings in the history of architecture. Annmarie Adams uses the Royal Vicalong with other hospitalsto explore issues in architecture and medicine, including the role of gender and class in both fields and the transformation of patients into consumers.